The Connecticut Prison Association and the search for reformatory justice - Bates, Gordon S. (Driftless Connecticut series, 2017)
Introduction: two faces of justice -- Connecticut's cultural context, 1875 -- From Newgate Prison to Wethersfield State Prison, 1775-1875 -- Rehabilitation rekindled, 1875-1910 -- Continuity and regression, 1910-1933 -- Reform during the Maltbie era, 1933-1960 -- The culmination of progressive reform, 1960-1970 -- Rehabilitation's last hurrah, 1970-1980 -- The return of retributive justice, 1980-1990 -- The legacies of retribution, 1990-2000 -- Epilogue: five critical questions